2021
DOI: 10.1007/s13571-021-00268-9
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Model Selection for Longitudinal Count Data

Abstract: We explore the performance of three popular model-selection criteria for generalised linear mixed-effects models (GLMMs) for longitudinal count data (LCD). We focus on evaluating the conditional criteria (given the random effects) versus the marginal criteria (averaging over the random effects) in selecting the appropriate data-generating model. We advocate the use of marginal criteria, since Bayesian statisticians often use the conditional criteria despite previous warnings. We discuss how to compute the marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 49 publications
(85 reference statements)
2
4
0
Order By: Relevance
“…Additionally, McNeish and Stapleton (2016) suggested that 20 clusters with five or more observations per cluster might be sufficient if the model is estimated with restrictive maximum likelihood. Overall, the marginal criteria outperformed the conditional ones, which is in line with the other results previously obtained in the literature (see Ariyo et al, 2019a, 2019, 2021; Chan & Grant, 2016b; Merkle et al, 2018; Quintero & Lesaffre, 2018).…”
Section: Simulation Studiessupporting
confidence: 91%
See 4 more Smart Citations
“…Additionally, McNeish and Stapleton (2016) suggested that 20 clusters with five or more observations per cluster might be sufficient if the model is estimated with restrictive maximum likelihood. Overall, the marginal criteria outperformed the conditional ones, which is in line with the other results previously obtained in the literature (see Ariyo et al, 2019a, 2019, 2021; Chan & Grant, 2016b; Merkle et al, 2018; Quintero & Lesaffre, 2018).…”
Section: Simulation Studiessupporting
confidence: 91%
“…However, there is still no consensus about the best criterion for model selection in a Bayesian context. For the distinction between the performance of the marginal against the conditional criteria, other authors have shown that marginal criteria outperform the conditional criteria in most settings for LMMs with some extensions (Ariyo et al, 2019a, 2019) and generalised linear mixed models (GLMMs) (Ariyo et al, 2021; Millar, 2018; Quintero & Lesaffre, 2018). This is also true for an item response model (Li, Qiu, Zhang, & Feng, 2016; Merkle et al, 2018; Millar, 2018).…”
Section: Bayesian Model Selectionmentioning
confidence: 99%
See 3 more Smart Citations